(untitled) (International Journal of Food and Nutritional Sciences, 2023)
People’s physical and mental health is being negatively affected by the widespread presence of stressful lifestyles in today’s fast-paced society. This abstract investigates the link between stressful lifestyles and yoga as a means of relieving stress and improving health. Anxiety, depression, and cardiovascular disease are just some of the health problems that have been linked to stressful lifestyles including extended work hours, technology overload, and social demands. Yoga, a centuries-old Indian practise, takes a comprehensive view of these contemporary issues. It includes physical postures, breath regulation, meditation, and mindfulness practises that work together to alleviate stress. The stress response mechanisms in the body may be modulated, relaxation can be induced, and emotional resilience can be strengthened by regular yoga practise, as shown by scientific studies. In addition, yoga raises one’s level of self-awareness, which in turn motivates one to adopt a more healthful way of life and put more emphasis on self-care. This abstract highlights the value of incorporating yoga into modern lives as a stress reliever and health booster. As more and more research demonstrates yoga’s positive effects, it must be seriously considered as a resource for those seeking equilibrium and fortification against the stresses of modern life.